Knowledge and Attitude Towards Corporal Punishment Among Primary School Teachers of Biratnagar Sub-Metropolitan City, Morang, Nepal - Shrestha, Menuka; Badhu, Angur; Shah, Tara; Baral, Dharanidhar (Birat Journal of Health Sciences, 2018)
Introduction: School experience has remarkable effect on emotional and personal development of children. Intended developments can be achieved through qualified education. It is quite a challenging fact that corporal punishment is still being used in the schools of Nepal as reported in the news papers and other literature. However, there is littlie information about the knowledge and atitude of teachers towards corporal punishment. Objecive: To assess knowledge and atitude and to identify the association between the selected variables and knowledge and attitude towards corporal punishment among primary school teachers of Biratnagar Sub-Metropolitan City. Methodology Descriptive cross-sectional study was conducted in Biratnagar Sub-metropolitan City, Nepal. A total of 160 primary school teachers were included using total enumeration sampling technique. Data were collected by using self-administered, semi-structured questionnaire and Likert Scale. Written consent was taken from each participant and ethical approval was taken from Institutional Review Board of B.P Koirala Institute of Health Sciences. Statistical analysis was done using SPSS. Results All respondents had heard about corporal punishment but most of them were not clear about the rules against corporal punishment in schools. The mean percentage score of knowledge was 58.81 ± 19.34 and for attitude 56.30 ± 6.98. There was a positive correlation (r=0.455, p <0.001) between knowledge and attitude towards corporal punishment. Majority of respondents scored less than the mean score. Females and government school teachers’ knowledge and attitude were found to be more positive. Conclusion The study revealed that the teaching experience, training regarding corporal punishment and childhood experience of corporal punishment were significantly associated with teachers’ knowledge and attitude. The government should begin public awareness campaigns to disseminate information on corporal punishment as violence through different media. Birat Journal of Health Sciences Vol.2/No.3/Issue 4/Sep- Dec 2017, Page: 248-254